On the biosynthetic origin of carminic acid. (May 2018) - Rasmussen, Silas A.; Kongstad, Kenneth T.; Khorsand-Jamal, Paiman; Kannangara, Rubini Maya; Nafisi, Majse; Van Dam, Alex; Bennedsen, Mads; Madsen, Bjørn; Okkels, Finn; Gotfredsen, Charlotte H.; Staerk, Dan; Thrane, Ulf; et al.
Abstract: The chemical composition of the scale insect Dactylopius coccus was analyzed with the aim to discover new possible intermediates in the biosynthesis of carminic acid. UPLC-DAD/HRMS analyses of fresh and dried insects resulted in the identification of three novel carminic acid analogues and the verification of several previously described intermediates. Structural elucidation revealed that the three novel compounds were desoxyerythrolaccin- O -glucosyl (DE- O -Glc p ), 5, 6-didehydroxyerythrolaccin 3- O -β-D-glucopyranoside (DDE-3- O -Glc p ), and flavokermesic acid anthrone (FKA ). The finding ofFKA in D. coccus provides solid evidence of a polyketide, rather than a shikimate, origin of coccid pigments. Based on the newly identified compounds, we present a detailed biosynthetic scheme that accounts for the formation of carminic acid (CA ) in D. coccus and all described coccid pigments which share a flavokermesic acid (FK ) core. Detection of coccid pigment intermediates in members of the Planococcus (mealybugs) and Pseudaulacaspis genera shows that the ability to form these pigments is taxonomically more widely spread than previously documented. The shared core-FK -biosynthetic pathway and wider taxonomic distribution suggests a common evolutionary origin for the trait in all coccid dye producing insect species. Graphical abstract: Highlights: Two novel coccid pigment intermediates isolated from Dactylopius coccus, including flavokermesic acid anthrone. Detection of the anthrone provides solid evidence for biosynthesis via the polyketide biosynthetic pathway. Coccid pigment production is much wider spread within the Coccoidea superfamily than previously believed.